Presentation through Graphs or Thinking in Pictures - Sahagal, Supranshu (Journal of Commerce and Trade, 2011)
The great problem of every teacher is to present facts in such a way that the students cannot help seeing what is meant. A bald statement is soon forgotten. Vivid images remain in the memory. Many people must have noticed the difference between reading a history text-book and seeing an historical film. Whatever the relative accuracy of the book and the film, the film certainly makes one realize events more intensely, and remember them longer. In films it is sometimes necessary to explain quite complicated ideas, not to a class of students, but to an audience which represents the whole population of a country. Cinema audiences, too, are in no mood for concentrated thought. They want to relax, to be amused. It is extremely instructive to examine how film directors go about the job. They rarely fail to make their point understood-a fact which should be seriously considered by those defeatists in education whose perpetual alibi is the stupidity of pupils.